EXTENDED ELASTIC IMPEDANCE INVERSION TO IDENTIFICATION LITOLOGY AND FLUID IN GAS SANDSTONE RESERVOIR AT WALAWALA FIELD NORTH SUMATRA BASIN - MAULANA HADI (NIM 22306301); Pembimbing: Dr. Sigit Sukmono dan Dr. Waluyo, JOHAN
Extended Elastic Impedance (EEI) inversion technique has been applied to reservoir characterization at Walawala field, North Sumatra Basin. The target zone is gas reservoir which has sand transgresive environment of sedimentation.